'It was like more easier': Rangatahi (Young People) and Their whānau (Family) Talk About Communication Assistance in the New Zealand Youth Justice System. (August 2021) - Howard, Kelly; McCann, Clare; Dudley, Margaret
This qualitative study gives voice to rangatahi (young people) and their whānau (families) (n = 10) who have experienced communication assistance in the New Zealand youth justice system. Communication assistance is a form of specialist support for witnesses and defendants who have been identified as having communication difficulties; and is modelled on the role of the intermediary in England and Wales. The findings overall suggest that communication assistance has a valuable and ongoing role to play in the NZ youth justice system, and may be one means of addressing the rights and needs of those with communication difficulties who offend.